2021
DOI: 10.1016/j.toxcx.2021.100078
|View full text |Cite
|
Sign up to set email alerts
|

Delays, fears and training needs: Perspectives of health workers on clinical management of snakebite revealed by a qualitative study in Kitui County, Kenya

Abstract: Key aims of the WHO Strategy to halve snakebite morbidity and mortality include health system strengthening and training of health workers. This requires knowledge of local health system needs and capacity, health worker training needs, and factors influencing health worker decision-making in snakebite management. This study explored health worker experiences and perceptions of snakebite management, both individually and in the context of their local health system. We used a qualitative study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Reducing the burden of snakebites requires preventing them from occurring in the first place and managing them effectively when they do occur. Previous studies have revealed a delay in seeking hospital treatment following a snakebite, with patients using traditional early intervention measures such as tourniquets, incision at the bite site, ingestion of medicinal herbs or application of the black stone [9,10]. Some victims use these remedies at home while others prefer to consult traditional healers with experience in assisting snakebite victims.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the burden of snakebites requires preventing them from occurring in the first place and managing them effectively when they do occur. Previous studies have revealed a delay in seeking hospital treatment following a snakebite, with patients using traditional early intervention measures such as tourniquets, incision at the bite site, ingestion of medicinal herbs or application of the black stone [9,10]. Some victims use these remedies at home while others prefer to consult traditional healers with experience in assisting snakebite victims.…”
Section: Introductionmentioning
confidence: 99%
“…According to this survey, only 5,412 (43.02%) medical staff had received training in the diagnosis and treatment of snakebite, and the score of snakebite diagnosis and treatment knowledge of medical staff who had received training was only 3.77 ± 2.11. Snakebite is a critical emergency, and medical staff’s knowledge of diagnosis and treatment is a guarantee of the provision of high-quality medical services [ 22 ]. It is well-established that access to high-quality healthcare services can improve snakebite survival rates, reduce disability, and decrease sequelae [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Masoud Yousefi 1,2* , Saeed Hosseinian Yousefkhani 1 , Marc Grünig 3 , Anooshe Kafash 4 , Mahdi Rajabizadeh 5,6 & Eskandar Rastegar Pouyani 7 Snakebite is one of the largest risks from wildlife, however little is known about venomous snake distribution, spatial variation in snakebite risk, potential changes in snakebite risk pattern due to climate change, and vulnerable human population. As a consequence, management and prevention of snakebite is hampered by this lack of information.…”
Section: Identifying High Snakebite Risk Area Under Climate Change Fo...mentioning
confidence: 99%
“…Up to 5 million snakebites occur each year leading to about 100,000 deaths annualy 2,[4][5][6] . Despite recent attention to the challenge of snakebite 3,5,[7][8][9][10] little is known about the distribution of venomous snakes, and therefore the spatial variation in snakebite risk and accessibility of vulnerable human population to healthcare system 3 . Further, the potential shift of high risk areas for snakebite due to climate change remains unknown.…”
Section: Identifying High Snakebite Risk Area Under Climate Change Fo...mentioning
confidence: 99%